DETERMINANTS OF THE ADOPTION OF GOOD GOVERNANCE: EVIDENCES FROM ZAKAT INSTITUTIONS IN PADANG, INDONESIA - Ika Sari Wahyuni (Share: Jurnal Ekonomi dan Keuangan Islam, 2017)
Zakat is one of the fundamental principles of Islam and central to develop an economic system by enhancing socio-economic development. The importance of proper management and governance are challenges for these institutions. This study examined the determinants of the adoption of good governance practices in Zakat institutions in Padang, Indonesia. A total of 51 questionnaires were analyzed out of 135 that had been distributed. The data were analyzed using the Statistical Package for the Social Science (SPSS) for descriptive statistics and the hypothesis testing. The results showed that only size of Zakat institutions was related positively and significantly to the adoption of good governance principles in Padang, Indonesia. The age of the Zakat institution also had a positive, significant relationship with performance. The study also found that the level of adoption of good governance practices in Zakat institutions in Padang was quite low. =========================================== Faktor-faktor Penentu Implementasi Tata Kelola Pemerintahan yang Baik pada Lembaga-lembaga Zakat di Padang, Indonesia_________ Zakat merupakan salah satu prinsip dasar dalam Islam dan sentral untuk mengembangkan sistem ekonomi dengan meningkatkan pembangunan sosial ekonomi. Pentingnya pengelolaan dan tata kelola yang tepat adalah tantangan bagi institusi-institusi saat ini. Studi ini menguji faktor-faktor penentu penerapan praktik tata pemerintahan yang baik di lembaga-lembaga zakat di Padang, Indonesia. Sebanyak 51 kuesioner dianalisis dari 135 yang telah didistribusikan. Data dianalisis dengan menggunakan Statistical Package for the Social Science (SPSS) untuk statistik deskriptif dan pengujian hipotesis. Hasil penelitian menunjukkan bahwa hanya ukuran lembaga zakat yang terkait secara positif dan signifikan terhadap penerapan prinsip tata kelola pemerintahan yang baik di Padang, Indonesia. Zaman lembaga Zakat juga memiliki hubungan positif dan signifikan dengan kinerja. Studi tersebut juga menemukan bahwa tingkat penerapan praktik tata pemerintahan yang baik di lembaga-lembaga zakat di Padang cukup rendah.